RAPD Analysis, Plasmid Profiles, Antibiotic Resistance and Occurrence of the Van Genes in Enterococcus Species Isolated from Human And Poultry - Toosa, Haryanti (2001)
The purpose of this study was to evaluate the molecular relatedness of the Enterococcus spp. isolated among poultry and clinical samples. A total of 71 poultry isolates and 29 clinical isolates were examined in this study. The poultry samples obtained from market in Sri Serdang, Selangor and Makmal Kesihatan Awam Veterinar. Petaling Jaya, whereas the clinical samples were from Hospital Universiti. Kuala Lumpur. E. faecalis (41 of 71 , 58%) was the dominant species isolated from poultry samples. Besides that, E. faecium (3 of 71, 4%). E. casseliflavus (4 of 71, 6%), E. durans (18 of 71, 25%) and E. hirae (5 of 71, 7%) were also detected. Twenty-nine isolates from clinical samples were identified as E. faeca/is (19 isolates, 66%), E. faecium (8 isolates, 28%), E. mundtii (1 isolate, 3%) and E. raffinosus (1 isolate, 3%). All isolates were resistant against ceftazidime, erythromycin. kanamycin, nalidixic acid and streptomycin (100%). Clinical isolates also demonstrated high resistance to cephalothin, gentamicin and norf\oxacin (100%). Sixty-four of 71 poultry isolates, and 26 of 29 clinical isolates were resistant to vancomycin and this indicated high prevalence of vancomycin resistant enterococci detected among the isolates. All seventyone isolates from poultry exhibited multiple resistance with Multiple Antibiotic Resistance (MAR) indices ranging between 0.53 to 1.0 while for clinical isolates the range were between 0.6 to 0.86. These high MAR index suggests that ał the isolates originated from high risk sources. According to plasmid profile analysis. 29 plasmid patterns were observed among poultry isolates with the plasmid DNA bands ranging in sizes from 1.1 to 35.8 megadalton. The plasmid analysis among clinical isolates were grouped into 9 plasmid patterns ranging in sizes from 1.85 to 35.8 megadalton. RAPD-PCR has been used to generate polymorphic genomic fingerprints to discriminate the enterococci isolates. Two primers (GEN15008 and GEN15009) were chosen after screening a set of 10 primers. These two primers yield reproducible and typeable results in most isolates examined with the bands ranging in sizes from 0.25 kb to 5.0 kb. From the dendrogram generated to study the interspecific relatedness among the isolates. 2 main clusters were observed and further subdivided into several subclusters defining the genetic heterogeneity among the isolates. The vanA specific (732 bp) fragment was detected in 96 of 100 (96%) of the isolates. 29 (100%) of dinical isolates and 67 of 71 (94%) of poultry isolates were positive for vanA gene. 4 of 71 (6%) of poultry were positive for vanC2IC3 gene (439 bp). Isolates containing the vanS or vanC1 gene were not found.